Regulação microambiental de células epiteliais límbicas corneais de coelho expandidas sobre membrana amniótica humana desepitelizada: ênfase para a organização supramolecular dos maiores biopolímeros extracelulares - Valdetaro, Gisele Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The goal of this study was to evaluate whether procedures on cell culture alter the supraorganization of amniotic and limbal extracellular matrix (ECM). Anisotropic properties of fibrillar collagen and proteoglycans were studied, since they correspond to major extracellular biopolymers. Rabbit limbal explants were cultured on denuded human amniotic membrane (AM) for two, seven, and 15 days. Uncultured AM and limbus were used as controls. Birefringence parameters related to the supraorganization of collagen fibers, and spectral absorption and linear dichroism (LD) related to the supraorganization of proteoglycans were evaluated. All samples were evaluated on microscope equipped with polarized light, monochromatic filters with varying wavelengths, and digital video camera. Birefringence, absorbances and LD were quantified by using image analyses software (Image J®, NIH, USA). Studies on birefringence showed that parallelism degrees of amniotic collagen fibers were of 1.02 for the control group, 1.17 for the two days culture, 1.26 for the seven days culture, and 1.17 for the 15 days culture. In relation to limbal collagen fibers, parallelism degrees were of 1.33, 1.17, 1.25, and 1.44. Birefringence brightness contrasts of amniotic collagen fibers were of 2.0 for the control group, 13.25 for the two days culture, 19.26 for the seven days culture, and 13.23 for the 15 days culture. In relation to limbal collagen fibers, birefringence brightnesses were of 23.01, 13.39, 19.90, and 30.31. Interference colors due to anomalous birefringence dispersion were observed. Procedures on cell culture induced alterations in absorbance values related to proteoglycans from amniotic and limbal ECM. In all samples, except on those cultured for 15 days, the amniotic ECM showed negative DL values. The DL of limbal ECM varied between negative and positive values for all, except on two days culture

Por objetivos, estudaram-se procedimentos em cultivo celular e se eles alteram a supraorganização da matriz extracelular (MEC) amniótica e da límbica, considerando-se propriedades anisotrópicas dos biopolímeros em comum, isto é, colágenos fibrilares e proteoglicanos. Explantes límbicos de coelhos foram cultivados sobre fragmentos de membrana amniótica (MA) desepitelizada humana, por dois, sete e 15 dias. Fragmentos não cultivados de MA e de limbo foram usados como controles. Avaliaram-se parâmetros de birrefringência em fibras colágenas e de absorção e de dicroísmo linear (LD) em proteoglicanos, da MEC amniótica e da límbica. Todas as análises foram conduzidas em microscópio óptico munido de luz polarizada, filtros monocromadores com diferentes comprimentos de onda e vídeo-câmera. Empregaram-se procedimentos em análise digital de imagens (software Image J®, NIH, USA). Parâmetros de birrefringência revelaram que os graus de paralelismo das fibras colágenas amnióticas foram de 1,02 nos controles, 1,17 nas amostras cultivadas por dois dias, 1,26 nas amostras cultivadas por sete dias e de 1,17 nas amostras cultivadas por 15 dias. Relativamente às fibras límbicas, foram de 1,33, 1,17, 1,25 e 1,44. Os contrastes dos brilhos das birrefringências das fibras amnióticas foram de 2,0 nos controles, 13,25 nas amostras cultivadas por dois dias, 19,26 nas amostras cultivadas por sete dias e de 13,23 nas amostras cultivadas por 15 dias. Relativamente às fibras límbicas, foram de 23,01, 13,39, 19,90 e 30,31. Cores de interferência causadas por dispersão anômala de birrefringência foram detectadas. Procedimentos em cultivo celular alteraram parâmetros absorciométricos relacionados à supraorganização dos proteoglicanos da MEC amniótica e da límbica. As MAs de todas as amostras, exceto as cultivadas por 15 dias, apresentaram-se com valores negativos de DL. Os valores de DL dos limbos de todas as amostras, exceto...
Keywords: Coelho; Colageno; Matriz extracelular; Proteoglicanos; Olhos; Proteoglycans